ANALISIS AJARAN KITAB 1 TESALONIKA 5:1 - 11 KEPASTIAN JANJI TUHAN DIDASARKAN ATAS KEYAKINAN PADA KITAB SUCI-NYA - Nainggolan, Bartolomeus Diaz (Fakultas Filsafat Universitas Advent Indonesia, 2020)
Paul invites everyone to make a commitment to be ready for His coming. When weaccept the gospel and become a child of light, when we live the truth of the gospel infaith, our hope and love can grow more similar in the image of Christ.